ETHNO DESIGN OF RESTAURANTS: MODERN EXPERIENCE AND MAIN CHARACTERISTICS - Абизов, В. А.; Сьомкін , С. О. (Art and Design, 2024)
The aim of the study. Identification of the main characteristics of the creation of modern ethno-design of restaurants, highlighting the characteristic features of various ethnic features in the interior design of public catering establishments based on the analysis of the creativity of Ukrainian and foreign designers Research methodology. The research is based on the method of comprehensive analysis and synthesis of objective data from available sources of information. The analytical part is based on thematic publications and Internet resources, as well as the authors' own experience. The methods of examinations, comparative and typological analysis were also used. Research results. The modern experience of creating ethno design of restaurants was analyzed and its characteristic features in different countries of the world and Ukraine were revealed. The connection of ethnic design with the preservation of cultural heritage and the use of regional products is considered. The main characteristics and key features of ethno design of food establishments are highlighted. Scientific novelty. Based on modern design and construction experience and analysis of literary sources, the place of Ukrainian ethnic design in the world space is outlined, the key characteristics of the creation of modern ethnic design of restaurants are defined and formulated. Practical significance. The conducted analysis will contribute to the formation of comprehensive practical recommendations for the future development of public catering establishments in the style of ethnic design and will help to generalize the features of the creation of modern ethnic design. The results of the conducted research can be used in the practice of design, reconstruction and construction of restaurants.